2016
DOI: 10.3390/catal6120193
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Cu-g-C3N4/AC Catalyst for Acetylene Hydrochlorination

Abstract: Abstract:A novel catalyst based on g-C 3 N 4 /activated carbon was prepared by adding CuCl 2 . The catalytic performance of the as-prepared catalyst was investigated in the acetylene hydrochlorination reaction. X-ray photoelectron spectroscopy, temperature programmed desorption, low temperature N 2 adsorption/desorption (Brunauer-Emmett-Teller), and thermal gravity analysis showed that Cu-g-C 3 N 4 /AC significantly enhanced the catalytic performance of the original catalyst by increasing the relative pyrrolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Such an optimisation will be particularly effective for surveys like eBOSS which spans a wide range of redshift. A similar z-weighting technique is also likely to be efficient in improving growth rate measurements from the RSD signal (Zhao et al 2015a;Ruggeri et al 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Such an optimisation will be particularly effective for surveys like eBOSS which spans a wide range of redshift. A similar z-weighting technique is also likely to be efficient in improving growth rate measurements from the RSD signal (Zhao et al 2015a;Ruggeri et al 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In previous studies of numerous metal chlorides and carbon catalytic materials,, activated carbon‐supported AuCl 3 catalyst (AuCl 3 /AC) as a green and efficient non‐mercury catalyst is considered to be most promising alternative to HgCl 2 /AC catalyst for acetylene hydrochlorination ,. Compared with HgCl 2 /AC catalyst, AuCl 3 /AC catalyst exhibits better initial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al . found that the Cu‐g‐C 3 N 4 significantly enhance the activity performance of CuCl 2 /AC catalysts, due to increasing the pyrrolic N content in Cu‐based catalysts . Moreover, Li et al .…”
Section: Introductionmentioning
confidence: 99%